Zakat and poverty alleviation in a secular state: the case of Muslim minorities in the Philippines - Gamon, Alizaman Dumangcag; Tagaranao, Mariam Saidona (Studia Islamika, 2018)
Poverty. Despite of having a well-crafted government model for poverty alleviation, the state roles in managing charities to alleviate people’s sufferance from economic deprivation are very minimal. By reason of the state’s strict adherence to secularism, the operation of Islamic institutions at the social level is deemed unconstitutional. It is unfortunate that the dynamics of Islamic social financial institutions i.e. zakat, waqf and sadaqah are not reflected in the economic road map for the reconstruction of Autonomous Region in Muslim Mindanao, particularly the rehabilitation of Marawi City after the war. This study examines the initiatives taken by government agencies and Muslim organizations towards the gradual revival of zakat as an Islamic social financial institution. In addition, the study highlights issues on the management of zakat and its role in poverty alleviation within the context of a secular state. The methodology used is based on qualitative method through documents analysis. This study found out that due to mismanagement, zakat fails to eliminate or reduce the poverty of the Muslim minorities in the Philippines.